Asking The Right Questions : Tips and Suggestions for Psychiatric Interview for Medical Students - Ang, Ai Ling (UNIMAS Publisher, 2020)
The idea to develop a booklet on psychiatric interview came from working with medical students and identifying their needs for a concise, quick reference guide on psychiatric interview questions. Although psychiatric history taking has similar principles and structure as general medical history taking, it focuses on a different range of symptoms and consequently, the questions to be asked. Basic training in psychiatry varies widely between medical schools worldwide, with the shortest duration being 2 weeks in a 6-year medical program, based on a quick survey among my colleagues and medical students I met from all over the world. Having received referrals from doctors working in emergency department of remote hospitals who had difficulty to giving sufficient vital psychiatric history such as regarding psychotic symptoms and suicidal ideation, I had to resist the urge to walk them through the whole process of psychiatric interview but it was highly impracticle in the (usually late night) phone consultations. I could only guide them through the essential questions for immediate management of the patient. It is understandably overwhelming to manage an emergency department in remote hospitals without adequate psychiatric interview skills, and it might prove stressful for the consultant on call who had to make important management decisions based on the information provided by the frontline doctors. My hope is that this quick-reference guide on psychiatric interview questions may be of benefit to medical students, frontline doctors in remote hospitals and allied health care professionals.